"What page, Miss?" Enhancing Text Accessibility with DAISY (Digital Accessible Information SYstem). (May 2014) - Spooner, Sue
Introduction: The provision of specially formatted materials is a complex and increasingly difficult task, given the extensive and burgeoning range of texts and resources available for classroom use. The need to extend the provision of accessible formats to include digital resources (in addition to braille, audio, and large print) led to a study that examined the benefits of providing curriculum materials in DAISY (Digital Accessible Information SYstem). The pilot study—Enhancing Text Accessibility for New Zealand Students, which was undertaken in 2008 and 2009—was designed as a qualitative study to determine the advantages and disadvantages of DAISY books compared with traditional formats and to evaluate the DAISY-related training needs of students and support staff members. Method: Purposive sampling was used to select participants who were identified by resource teachers employed by the Blind and Low Vision Education Network New Zealand (BLENNZ) and the Manurewa High School Vision Resource Room. A total of 12 students in years 7–10 attending secondary schools and 13 support personnel took part in the study, which involved training, interviews, and focus group sessions. Results: The overall response to DAISY was very positive, with a number of advantages over traditional formats identified. Participants were satisfied with the DAISY training they had received and reported high levels of confidence and competence in using DAISY. Discussion: Significant variables were identified as affecting the use of DAISY, including student preferences, abilities, and motivation; availability of DAISY text; reliability of and support for technology; and the provision of appropriate training in DAISY. Implications for practitioners: DAISY books provide a valuable adjunct to traditional accessible formats and should be a considered an option for students with visual impairments as part of their literacy provisions or "toolbox."